The Causal Role of the Dorsolateral Prefrontal Cortex in the Modification of Attentional Bias: Evidence from Transcranial Direct Current Stimulation - Clarke, Patrick; Browning, M.; Hammond, G.; Notebaert, L.; MacLeod, C. (Elsevier Inc., 2014)
Background: A pattern of attentional bias for threatening information is thought to be involved in the etiology of anxiety. Consistent with this idea, cognitive training techniques directly targeting such patterns of biased attention have been shown to reduce symptoms of anxiety. Research seeking to establish the neurologic underpinnings of change in the attentional bias for threat have implicated, but not confirmed, the role of lateral prefrontal regions. Methods: The current study sought to confirm experimentally the causal role of lateral prefrontal areas in the modification of attentional bias by delivering targeted cortical stimulation during attention bias modification training to assess the consequent effects on attentional bias change. While completing either an “attend threat” or “avoid threat” attention bias modification task, 77 volunteers (17–22 per group) received either active transcranial direct current stimulation of the left dorsolateral prefrontal cortex or a sham stimulation control condition. Results: Participants receiving active stimulation showed greater evidence of attentional bias acquisition in the targeted direction (toward or away from threat) compared with participants in the sham stimulation condition. Conclusions: Our findings provide the first experimental evidence that increasing activity in the dorsolateral prefrontal cortex leads to greater evidence of attention bias modification. This evidence confirms the role of these areas in facilitating change in the allocation of attention to threat. We believe this study provides a critical step in the translation of neuroimaging findings to novel neuromodulatory interventions capable of enhancing the treatment of emotional pathology.